Coding of COPD Exacerbations and the Implications on Clinical Practice, Audit and Research. (1st November 2020) - Echevarria, C.; Steer, J.; Bourke, S. C.
Abstract: International Classification of Disease 10 (ICD-10) codes record hospital admissions. We aimed to measure the accuracy of COPD exacerbation (ECOPD) codes and examine coding practices for COPD exacerbation. Prospective screening and ICD-10 codes were used to identify potential ECOPD within the DECAF internal validation cohort. Two coding searches were performed. The first search identified patients with an ECOPD discharge code, and a second, broad search was developed to identify all clinically confirmed ECOPD. 717 of 1, 122 (64%) patients with an ECOPD code had confirmed ECOPD. Common reasons for misclassification in the 405 patients who did not have an ECOPD included: lack of obstructive spirometry to diagnose COPD; and hospital admission due to progressive malignancy, asthma or cardiovascular disease. The broad search identified an additional 297 patients with ECOPD missed by the ECOPD codes. The vast majority of this group had pneumonia complicating ECOPD. ECOPD codes are insufficiently reliable to identify patients with clinically confirmed ECOPD for the purposes of audit or research. Search strategies should include pneumonia codes, specialist review of medical notes and spirometry confirmation of COPD.